Ashwagandha (Withania somnifera) - Its Antibacterial and Anticancer Activity - Mazurkiewicz, Aleksandra; Mądry, Wojciech; Kołodziej, Magdalena; Męczyńska, Joanna; Saiuk, Nazarii; Kozicz, Michał Andrzej; Seredyński, Tomasz; Wojciechowska, Adriana; Marcicka, Justyna; Salasa, Weronika (Journal of Education, Health and Sport, 2024)
Introduction Ashwagandha, a traditional Indian plant, is gaining increasive attention from scientists worldwide due to its potential health benefits, especially in the context of its antibacterial and anticancer properties. Aim of the study The aim of this review was to discuss recent findings regarding the impact of Withania Somnifera on antibacterial effect and its potential applications in anticancer therapy. Materials and methods: The paper was created based on the Pubmed and Google Scholar database. The literature was reviewed using the keywards: , Ashwagandha”, , Withania Somnifera”, , antibacterial ”, , anticancer”, , side effects”, , breats cancer”. Results Studies have confirmed Withania Somnifera, exhibits significant anticacterial and anticancer effects. It inhibits the growth of both Gram-negative and Gram-positive bacteria. Futhermore, it demonstrates anticancer activity, especially in breast cancer, by stimulating apoptosis, induction of cytotoxic effects on cancerous cells and increasing cell sensitivity to radiation. Conclusion Despite promising results, futher research on the benefits of Ashwagandha, particulary in the long term, is essential. There is growing need of more research of the potencial benefits of Ashwagandha in the treatment of various disorders including cancer and bacterial infections and to develop more effective therapeutic strategies. The need for large randomized studies comparing long term clinical effectiveness is emphasized